Observations of explosion phase boron nitride formed by emulsion detonation synthesis. (1st March 2018) - Örnek, Metin; Reddy, K. Madhav; Hwang, Chawon; Domnich, Vladislav; Burgess, Alan; Pratas, Silvio; Calado, Joao; Xie, Kelvin Y.; Miller, Steven L.; Hemker, Kevin J.; Haber, Richard A.
Abstract: Emulsion detonation synthesis (EDS) is a recently developed process to synthesize nano-sized ceramics based on detonation of two water-in-oil emulsions. The process produces high pressure and temperature along with fast cooling, thus providing ideal environment for metastable phase formation. Here we applied the process for the first time on hexagonal boron nitride (h-BN). Characterization studies demonstrated the formation of metastable explosion BN phase (e-BN) with grain sizes of 10–20 nm embedded in h-BN matrix. These findings support the potential use of EDS a novel and promising pathway for the synthesis of e-BN and other metastable BN phases. Graphical abstract: